When Might Does Not Create Religious Rights: For-Profit Corporations’ Employees and the Contraceptive Coverage Mandate - Benedict, Kathryn S. (Columbia Journal of Gender and Law, 2013)
It is classic Christian theology that “ye cannot serve God and mammon.” And yet, there are currently thirty-eight lawsuits pending that make the claim that not only does a for-profit corporation have religious rights, but also that the Patient Protection and Affordable Care Act Women’s Health Amendment’s contraceptive coverage mandate violates the Religious Freedom Restoration Act (RFRA) and the Free Exercise Clause of the First Amendment by infringing on for-profit corporations’ religious rights. This Note provides an in-depth look at the specific claims raised by for profit corporations challenging the contraceptive coverage mandate. Part I will first compare the legal standard under the Religious Freedom Restoration Act with the legal standard under the Free Exercise Clause of the First Amendment, an idiosyncrasy that stems from the Supreme Court’s watershed decision of Employment Division, Department of Human Resources of Oregon v Smith. Part I will also give a brief background of the Patient Protection and Affordable Care Act (ACA), the Women’s Health Amendment (WHA), and the contraceptive coverage mandate. Part II will provide a framework for analyzing the decisions issued so far, dividing the relevant arguments into three categories: corporations’ religious rights, RFRA, and the Free Exercise Clause. Part II will use those categories as a structure for discussing the courts’ analyses of the contraceptive coverage mandate. Lastly, Part III will address the three questions posed by these litigations using the categories developed in Part II, and will suggest that the key to answering these questions lies in recognizing the unrepresented but central interests of a third party in these lawsuits: the employees whose access to contraceptive services hangs in the balance.